The economic impact of Strategic Information Systems (SIS): a study of the commercial banking industry in the U.S. - Πολλάλης, Γιάννης Α. (SPOUDAI Journal of Economics and Business, 1998)
Information systems researchers have primarily relied on contingency models and frameworks to better understand how firms can use the capabilities of information technology (IT) and thus take advantage of opportunities, or protect themselves from the threats of the environment. The results of that dominant research effort have advanced knowledge regarding the external impacts of IT, but have not helped very much to create explanatory models that deal with the interactions between the IT-dependent elements of organizations and with the economic impact of those interactions. This paper suggests, develops and tests such an explanatory and predictive model of IT-BASED economic impact by distinguishing three types of organizational systems integration that impact the performance of US commercial banks: Technological Integration, Functional Integration, and Strategic Integration. The results of this study yield some useful set of guidelines: most interesting is the role of consistency between an organization's business and strategic information systems (SIS) plans to improve overall firm performance. Other recommendations include having a high degree of involvement of IS executives in corporate planning, the use of outsourcing services to promote systems integration, and the importance of internal coordination mechanisms to facilitate both systems consistency and lower transaction costs.